Review: A study on pet facilitated therapy (PFT) in mental health disorders. - Cho Cho Zaw, Cho Cho Zaw; Ahmad, Norfadzilah; Min @ Mohd Omar, Myat (SAS Publishers, India, 2019)
Mental health is a level of psychological well-being or an absence of mental illness. According to WHO (2014), it is the “a state of well-being in which every individual realizes his or her own potential, can cope with the normal stresses of life, can work productively and fruitfully, and is able to make a contribution to her or his community”, or “a focus on the absence of disease to the attainment of one’s potential” (Lundy and Janes, 2009). Apart from the conventional medicine and treatment, the alternative treatment such as music therapy, diet, exercises and others are considered as complementary treatment for the clients nowadays. Since the benefits of complementary and alternative therapies have been proven it should not be excluded in caring the client with mental health problems. As the latest trend, PFT has been increasingly used as part of the therapy in treating the clients with various health problems. Thus, this study is aimed to explore the potential benefits of PFT in the client with mental health problems and issues. The findings indicated the benefits of PFT and suggested the use of PFT in care of clients with mental health setting after careful removal of the risks involved and considering the limitations. It is hoped that this study will help improves awareness among the public as well as the health care professions who are dealing with the mental health clients.